A survey on database intrusion detection: approaches, challenges and application. (16th January 2020) - Jindal, Rajni; Singh, Indu
Databases store vital information of an organisation and are therefore integral for its efficient working. This necessitates the establishment of database intrusion detection systems (DIDSs) which can detect and prevent unauthorised user access to the critical information stored in database. A lot of work has been done in the field of DIDSs which has grown at a very rapid pace. A large number of publications emerging every year to further improve upon the existing state of the art solutions. This paper investigates research on major approaches proposed in the field of database intrusion detection and analyses the drawbacks of the proposed methods in order to drive future research towards more efficient and effective DIDSs. A systematic survey is conducted in order to classify various approaches for detecting intrusion in databases. The work identifies open research questions and challenges, by methodically comparing existing strategies to combat malicious transactions in a database system, and also provides an insight to the applications of DIDSs.